2013
DOI: 10.1038/ncomms3746
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium selectivity alone does not create K+-selective ion conduction in K+ channels

Abstract: Potassium (K þ ) channels are selective for K þ over Na þ ions during their transport across membranes. We and others have previously shown that tetrameric K þ channels are primarily occupied by K þ ions in their selectivity filters under physiological conditions, demonstrating the channel's intrinsic equilibrium preference for K þ ions. Based on this observation, we hypothesize that the preference for K þ ions over Na þ ions in the filter determines its selectivity during ion conduction. Here, we ask whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 46 publications
7
46
0
Order By: Relevance
“…The integrated heat change from each injection was fit to a binding isotherm to reveal apparent K d values of 0.16 mM and 0.13 mM for OM1-ΔC and OM2-ΔC, respectively, which is similar to the apparent K d value for WT-ΔC of 0.15 mM (38). Because these apparent K d values reflect the competition between Na + and K + in the chamber, we varied the concentration of Na + ions in the chamber to obtain the K + ion affinity in the absence of Na + ions (29,38,39). The apparent K d values were then fit to a competition equation to obtain (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The integrated heat change from each injection was fit to a binding isotherm to reveal apparent K d values of 0.16 mM and 0.13 mM for OM1-ΔC and OM2-ΔC, respectively, which is similar to the apparent K d value for WT-ΔC of 0.15 mM (38). Because these apparent K d values reflect the competition between Na + and K + in the chamber, we varied the concentration of Na + ions in the chamber to obtain the K + ion affinity in the absence of Na + ions (29,38,39). The apparent K d values were then fit to a competition equation to obtain (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…With KdpB in the E1 conformation, as observed in the structure, K + ions enter the selectivity filter of KdpA from the periplasmic side of the membrane. Selectivity filters have innate binding affinity for K + ions at the μM level28 and the relatively slow rate of transport by KdpFABC would allow equilibration of these sites and explain the selectivity of K + over Na + . Permeation of ions into the S4 site would induce a proton charge transfer through the tunnel to the structural water molecule bound to the canonical ion binding site in KdpB.…”
mentioning
confidence: 99%
“…Based on the crystallographic titration experiments, the NaK2K construct has two high-affinity K + sites while the NaK2CNG construct has only one K + -selective site. These experiments show that both K + -selective and non-selective channels select K + over Na + ions at equilibrium, implying that equilibrium selectivity is insufficient to determine the selectivity of ion permeation (16, 17). The data indicate that having multiple K + ions bound simultaneously is required for selective K + conduction, and that a reduction in the number of bound K + ions destroys the multi-ion selectivity mechanism utilized by K + channels.…”
Section: Introductionmentioning
confidence: 93%
“…By examining the properties of MthK(13) and NaK (14, 15) mutants, Jiang and co-workers showed that the channel becomes selective only if four consecutive binding sites exist along the narrow selectivity filter. This has culminated more recently with studies of two engineered mutants of the NaK channel, referred to as “NaK2K” and “NaK2CNG” (16, 17). According to reversal potential measurements from single-channel electrophysiology, the NaK2K construct is K + -selective and the NaK2CNG construct is non-selective.…”
Section: Introductionmentioning
confidence: 99%